The Role of Technology-Based Learning in Mediating the Influence of Cultural Diversity Perception on Students’ Inclusive Attitudes - Suyuti; Andi Fitriani Djollong; Yulian Purnama; Heppy Sapulete; Feby Arief Nugroho (Jurusan Teknik Informatika dan Komputer, 2025)
This study investigates the mediating role of technology-based learning in the relationship between students’ perception of cultural diversity and their inclusive attitudes in Jakarta’s multi-campus higher-education environment. Using a quantitative explanatory design, data were collected from 280 students across five universities—Universitas Indonesia, Universitas Negeri Jakarta, BINUS University, Universitas Katolik Atma Jaya, and Universitas Tarumanagara—through a Likert-scale survey. The variables measured included perception of cultural diversity (X), technology-based learning (Z), and inclusive attitude (Y). Data were analyzed using multiple regression with mediation testing via the Baron and Kenny (1986) approach and Sobel test using SPSS 26. The results reveal that perception of cultural diversity significantly predicts both technology-based learning (β = 0.55, p < 0.001) and inclusive attitude (β = 0.42, p < 0.001). When the mediator is included, the direct effect decreases to β = 0.19, while the indirect effect remains significant (Sobel z = 5.98, p < 0.001), confirming partial mediation. The inclusion of the mediator also increases the model’s explanatory power (ΔR² = 0.16). These findings indicate that digital learning environments act as catalysts that convert intercultural awareness into inclusive behavior through collaborative and reflective online experiences. The study concludes that fostering inclusive attitudes requires both positive cultural perception and deliberate integration of inclusive digital pedagogy. It contributes to theoretical understanding of digital mediation and provides practical insights for curriculum design and institutional policy in promoting inclusive education